MASKING OF OUTPUT SIGNAL, DETERMINING MINIMAL LEVEL OF MASKING NOISE - PAVLENKO, YEVHEN; STEPANOV, MIKHAILO (Herald of Khmelnytskyi National University. Technical sciences, 2023)
This paper considers one of the potential ways of protecting the output signal which goes beyond the controlled zone, as a result of one possible case of signal detection against background noise by interception receiver based on mathematical model of leakage information using radio engineering intelligence. First part considers the main provisions of used mathematical model and describes the process of converting electromagnetic oscillation received by interception receiver in order to make a decision about signal presence, presented an inequality for making decision about the presence or absence of  deterministic signal against background of white noise, given a functional diagram of optimal receiver  which performs the specified operations, described signal/noise ratio and probability of signal detection by optimal receiver, considered graphical dependence probability of signal detection by optimal receiver with signal/noise ratio, considered one of the possible variants of signal detection by receiver against background noise based on which in the second part presented a potential way of protection the output signal.Second part considers the possibility of preventing the interception of information by means of technical intelligence by masking signals that go beyond the controlled zone by means of specifically formed noise, presented structural diagram of interception the output signal by means of technical intelligence without using masking noise, formed signal-to-noise ratio with absence or presence of active noise interference, determined minimal value of intensity level of masking interference, presented structural diagram of interception the output signal by means of technical intelligence using masking noise.
Keywords: technical protection of information; radio technical intelligence; masking noise; minimal level of masking signal; signal interception; controlled zone